(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
The article examines the theoretical foundations of linguopoetics as an interdisciplinary field of modern linguistics. Special attention is given to the relationship between language and literary text, the poetic function of language, and the role of concepts in shaping the national-cultural worldview. Based on the works of domestic and foreign scholars, various types of linguopoetics are analyzed, including phonetic, morphological, syntactic, semantic, and pragmatic linguopoetics. Examples from Uzbek and English literary texts are provided to demonstrate the manifestation of concepts and their ethnocultural characteristics. The study emphasizes the significance of linguopoetics in exploring literary texts, national consciousness, and cultural values